CULTURAL CONTENT AND CONTEXT IN THE TEXTBOOK â€œ WHEN ENGLISH RINGS A BELLâ€ USED BY GRADE SEVENTH STUDENTS OF SMP MANDIRI PONTIANAK - Zulkarnaen, .; ., Ikhsanudin; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research is to find the cultural content and context in the textbook ?When English Rings A Bell?. The method of this research is content analysis. There was one type of tool of colecting data in content analysis the researcher used matrix in cultural category based on malay culture perspective and interviewed the owner of Malay culture to get the information in source culture. The study finds that The books present mostly the source culture (Indonesian Culture) in comparison to target culture and international culture. This ratio is quite ideal as English is taught as a Foreign Language thus English textbook in Indonesian context are aimed at focusing more on local content while introducing the learners to the target culture and international. From the source culture there is 67 % Pontianak Malay content, it is indicated that the books is compatible in the culture context . Based on Littlejohn framework has been recomended to be used . Key Words: Textbook evaluation , Cultural content and context , Source culture. Abstrak Tujuan dari penelitian ini adalah untuk menemukan konten dan konteks budaya dalam buku ?When English Rings A Bell?. Metode penelitian ini adalah analisis konten. Ada satu jenis alat pengumpul data dalam analisis konten peneliti menggunakan matriks dalam kategori budaya berdasarkan perspektif budaya melayu dan mewawancarai pemilik budaya Melayu untuk mendapatkan informasi dalam budaya sumber. Studi ini menemukan bahwa Buku tersebut menyajikan sebagian besar budaya sumber (Budaya Indonesia) dibandingkan dengan menargetkan budaya (Inggris) dan budaya internasional. Rasio ini cukup ideal sebagai bahasa Inggris diajarkan sebagai bahasa asing sehingga buku teks bahasa Inggris dalam konteks Indonesia ditujukan untuk lebih fokus pada konten lokal sambil memperkenalkan para peserta didik dengan budaya target dan internasional. Dari budaya sumber ada 67% konten Melayu Pontianak, dalam hal ini menunjukkan bahwa buku tersebut kompatibel dalam konteks budaya. Berdasarkan kerangka Littlejohn direkomendasikan untuk digunakan dalam penelitian ini. Kata kunci: Evaluasi buku teks, Konten dan kontek budaya, Budaya sumber